A simple fluorescence sensor for the detection of nitrite (NO2−) in real samples using water-dispersible graphite-like carbon nitride (w-g-C3N4) nanomaterials. (26th June 2017) - Chen, Jing; Ma, Qin; Wang, Caihe; Hu, Xiaoyan; Gao, Yunjing; Wang, Huan; Qin, Dongdong; Lu, Xiaoquan
Abstract : A novel NO2 − detection method based on the reaction of w-g-C3 N4 with nitrite (NO2 − ) in an acidic medium. Abstract : A novel strategy was developed for the fluorescence detection of nitrite (NO2 − ) in real samples. The method is based on the reaction of water-dispersible graphite-like carbon nitride (w-g-C3 N4 ) with nitrite (NO2 − ) in an acidic medium to form a new kind of weak fluorescence species. Under optimal conditions, the limit of detection (LOD) for nitrite (NO2 − ) detection was determined to be 0.16 nM (S/N = 3), and the relative fluorescence intensity versus logarithm concentration of nitrite (NO2 − ) showed good linearity in the range from 0 to 58.5 μM with R 2 = 0.997. This probe displayed several appealing properties including low-cost, simplicity and convenience, high sensitivity, and excellent selectivity.